Tuber, seed size and spacing on potato yield under field conditions - Queiroz, Luiz Raphael de Melo; Kawakami, Jackson; Muller, Marcelo Marques Lopes; Umburanas, Renan Caldas; Eschemback, Vlandiney (Comunicata Scientiae, 2013)
The seed tuber size and spacing plants are important in the productivity of the potato. The objectiveof this study was to evaluate the effect of different sizes of seed tubers and plant spacing on tuberyield of potato plants cultivar Agata. The experiment was conducted in a commercial potatocrop at Guarapuava-PR, from December, 2010. The treatments were constituted of three spacingbetween plants (20, 25, and 30 cm, plot), and two different types of seed (type I and type III, subplot),arranged in a split plot design in randomized block design with three replications. The characteristicsanalyzed were: yield and total number of tubers; yield, dry matter (MS) and number of commercialtubers separated into three size classes. There was no statistically significant difference for totaland commercial yield and commercial MS among the different planting spacing and potato seedtype. There was statistically significant difference among the different planting spacing for total andcommercial number of tubers, due to higher number of small tubers (<100 g) in plants from the lowestplanting spacing. The average weight of commercial tubers of plants from potato seed type III washigher than from type I. There was no significant interaction between the different planting spacingand types of tuber seed, suggesting that the use of potato seed type III and planting spacing of 30cm provides the best cost-benefit ratio for potato growers as it minimize the use of seed potatoes inthe field and reduce the costs of crop establishment.